FUTURE PROSPECT OF CDM SOLAR COOKER PROJECT ACEH 1, INDONESIA - suharta, herliyani (185P -3466)
Firewood in almost all rural areas uses firewood for cooking. Smoke exposure from firewood seriously affects the children's growth and the health of women, increasing woman burden and poverty. Its greenhouse gas (GHG) emissions contribute to global climate change. This is one of the greatest challenges of humanity. The CDM (Clean Development Mechanism) Solar Cooker Project in Sabang Islands and Badar city in South East Aceh was arranged to lay down a better energy path scenario for the future. Solar concentrator cookers "K14" and heat retaining containers named "Wonder box" will be transferred to the people. This project avoids 3.5 tonnes CO2 emissions per year per K14 and applies for a renewable crediting CER (carbon emission reduction) for 7 years period. The CER verification is described. Some views as a societal research finding within the CDM Solar Cooker Project Aceh 1 are described briefly.